DEVELOPMENT OF RELATIONSHIP MARKETING IN THE REPUBLIC OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2015)
In this article, the concept of relationship marketing practice and scope of the client and the resolution of conflicts arising between the contrast track.
Keywords: RELATIONSHIP MARKETING